Kerusakan membrana basalis pada hiperplasi prostat benigna, prostatic intraepithelial neoplasia dan adenokarsinoma prostat: Kajian kontinuitas kolagen tipe IV membrana basalis. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Basal membrane (BM), a selective permeable membrane is mainly composed of type IV collagen. A tumor invasion, therefore, may only occur if this membrane is destroyed by an active process of tumor producing proteolytic enzymes. It has been found that prostatic intraepithelial neoplasia (PIN) is a prostatic premalignant lesion. Although both benign prostate hyperplasia (BPH) and prostatic adenocarcinoma required an androgenic hormone for their growth, the correlation between the degree of destruction of basal membranes and BPH, PIN, and prostatic adenocarcinoma should be clarified. This can be studied by observing the continuity of periacinair BM. In order to understand the correlation among prostatic lesions, the BM continuity of 40 paraffin block specimens (15 BPH, 11 PIN, and 14 Prostatic adenocarcinomas) were studied. The BM of these specimens were stained immunohistochemically with MoAB anti human Type IV collagens. The periacinair BM continuity was scored 0-5. The Spearmans correlation test was used to analyze their possible relationship.The result shows that there is a significant correlation between the degree of destruction of basal membranes and BPH, PIN, and Prostatic adenocarcinomas (r = 0.898